Expert System That Detects COVID-19 Using Forward Chaining Algorithm: Expert System That Detects COVID-19 Using Forward Chaining Algorithm - Ibnu Akil (Jurnal Mantik, 2020)
The spread of Covid-19 disease since early year 2020 which caused by coronavirus has made the world in great pandemic. Besides the vaccine has not been discovered yet, it is also the cost for doing rapid test or polymerase chain reaction (PCR) are expensive. By using the information technology that is expert system, so the aim of this research is to develop expert system to detect Covid-19 disease based on the confirmed symptoms of Covid-19. This expert system will be using the algorithm of forward chaining.